Partisipasi Masyarakat dalam Meningkatkan Kualitas Sumber Daya Manusia melalui Program Beasiswa di Kabupaten Pandeglang - Tiffani Aulia Amanda (JURNAL ILMIAH ILMU ADMINISTRASI, 2025)
This study aims to examine community participation in improving the quality of human resources through the Village Scholars Scholarship Program in Pandeglang Regency. The main issue addressed in this research is the low level of community participation in the program, which is attributed to limited motivation and understanding of the program's objectives, as well as inadequate coordination and communication. The research employs a qualitative descriptive method, utilizing observation, interviews, and documentation as data collection techniques. The findings indicate that efforts to enhance participation through motivation are categorized as low, as only a small number of individuals are aware of the program's vision, mission, and objectives. Efforts to improve participation through coordination and communication are also classified as low, due to the lack of institutional support within the Village Scholars initiative. Similarly, efforts to enhance participation through task assignment and supervision are deemed low, as stringent oversight is lacking beyond the collaborative aspects of the program.